Novel sphingosine-1-phosphate lyase mutation causes multisystemic diseases: case report - Büyükyılmaz, Gönül; Adıgüzel, Keziban Toksoy; Aksoy, Özlem Yüksel; Kasapkara, Çiğdem Seher; Demir, Gizem Ürel; Demir, Engin; Ergun, Şule Berk; Gürbüz, Fatih; Boyraz, Mehmet (The Turkish Journal of Pediatrics, 2023)
Background. Sphingosine phosphate lyase insufficiency syndrome (SPLIS) caused by inactivating mutations in the human SGPL1 gene results in congenital nephrotic syndrome, adrenal insufficiency, ichthyosis, immunodeficiency, and a wide range of pathological neurological features. We present a novel mutation in the SGPL1 gene causing hypocalcemia, primary adrenal insufficiency (PAI), nephrotic syndrome, subclinical hypothyroidism, lymphopenia, ptosis, and pathologic neuroimaging findings. Case. A Turkish male infant presented with bruising at 2 months of age and was diagnosed with hypocalcemia, PAI, and subclinical hypothyroidism. At the age of 15 months, he was admitted to the hospital with ptosis. Other systemic manifestations included persistent lymphopenia and nephrotic syndrome. Magnetic resonance imaging (MRI) of the brain and orbit demonstrated asymmetric contrast enhancement in the left cavernosal sinus, orbital apex, and thinning at the bilateral optic nerve. Whole exome sequencing (WES) revealed a homozygous c.1432C > G (p.Gln478Glu) variant in the SGPL1 gene (NM_003901.4), which has not previously been reported in the literature. Conclusions. Novel mutations in SGPL1 are still being identified. This case reminded us that SPLIS should not be considered for patients with nephrotic syndrome alone. Still, PAI may also include patients with neurological disorders, hypocalcemia, and pathological neuroimaging findings such as thinning at the bilateral optic nerve.